An assessment of the effectiveness of revenue management practices on performance of local authorities. Case of municipality of marondera - Chikeya, Vimbayi J. (Midlands State University, 2017)
The main aim of this research was to assess the effectiveness of revenue management practices on performance of Local Authorities. The research looked at several revenue management practices exercised in Local Authorities but focusing on Municipality of Marondera. The statement of the problem highlighted that increases in adverse revenue variance are impacting negatively on the Council’s performance. The Council increased tariffs, replaced dark and faulty meters, increased the space for flea markets, expanded its on-going projects but still it continued to incur adverse variances. This has caused challenges in delivering services to the public and prompted the researcher to undertake this research. Literature review covered revenue management practices, how they are implemented, implementation controls, personnel attributes required, challenges being faced and the best practice in revenue management. The descriptive research survey was used and data was gathered, presented, analysed and interpreted. The findings showed that the Council does not practice indigent management, the practices are not communicated to employees, most of the Council’s controls are weak, there are no budgetary controls, personnel lacks the knowledge of information technology and industrial analysis skills and problems such as inadequate finance, lack of skills and capacity are affecting the Council’s revenue management. Recommendations were made that the Council should practice indigent management, engage into public private partnerships, formulate budgetary controls, monitor and modify internal controls, practice automated revenue collection and use value for money system in assessing the best way of delivering a service.